Instructor Presence in a Virtual Classroom - Tyrväinen Heli; Uotinen Sanna; Valkonen Leena (Open Education Studies, 2021)
Synchronous online learning platforms have been used actively during the COVID-19 period. They have opened possibilities for online learning and interaction, but have also posed new challenges for instructors. This article provides insights into one teacher’s interactions and examines how the instructor presence is expressed in the teachers’ activities in virtual classrooms in higher education. Instructor presence is investigated using the social and teaching presence indicators of the community of inquiry (CoI) framework. Twelve hours of interactions across six online classes were recorded, transcribed, and analysed using content analysis. The findings suggest that indicators of teaching presence dominate interactions in a virtual classroom, but it often involves co-occurrences of indicators of social presence. The typical features of instructor presence included addressing students by name, encouraging them, expressing gratitude for and acknowledging their contributions, describing actions on the dashboard, clarifying and summarising content, and responding to technical concerns. These findings may suggest holistic and pedagogical ways to understand and develop synchronous online interactions and teaching and learning practices. They also have implications for the skills instructors need in virtual classrooms.